2006
DOI: 10.1128/jcm.01087-06
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Enzyme Immunoassay for Detection of Sapovirus-Specific Antibodies and Its Application in a Study of Seroprevalence in Children

Abstract: Sapoviruses (SVs) are an important cause of acute pediatric gastroenteritis. Due to the lack of appropriate diagnostic methods, the epidemiology of SV-associated illness remains poorly understood. Baculovirus and Escherichia coli expression systems were evaluated for the development of antibody detection enzyme immunoassays (EIA). Age-related antibody prevalence in children was studied using the new EIA. Because of the low yield of the baculovirus system, the E. coli-expressed SV capsid proteins were used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
25
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 48 publications
4
25
2
Order By: Relevance
“…For our patients, the common predisposing factors were poor hygiene and low socioeconomic status, which may expose them to ectoparasites including lice and fl eas. In contrast with previous study fi ndings, B. quintana infectious endocarditis developed on preexisting valvular lesions in all patients (10). This fi nding may refl ect a different clinical evolution than in Europe, where studies have suggested that B. quintana infectious endocarditis followed chronic bacteremia in patients who did not have previous valvular defects (10).…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…For our patients, the common predisposing factors were poor hygiene and low socioeconomic status, which may expose them to ectoparasites including lice and fl eas. In contrast with previous study fi ndings, B. quintana infectious endocarditis developed on preexisting valvular lesions in all patients (10). This fi nding may refl ect a different clinical evolution than in Europe, where studies have suggested that B. quintana infectious endocarditis followed chronic bacteremia in patients who did not have previous valvular defects (10).…”
contrasting
confidence: 54%
“…quintana is mostly associated with human body lice but has also been found in fl eas (9). The predisposing factors for B. quintana endocarditis are homelessness, alcoholism, and exposure to body lice (10). For our patients, the common predisposing factors were poor hygiene and low socioeconomic status, which may expose them to ectoparasites including lice and fl eas.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…In contrast, very little information is available about protective immunity against sapovirus infection. Sera collected from naturally infected humans or immunized animals with recombinant VP1 protein of sapovirus were shown to be moderately cross-reactive against the heterologous genotypes and weakly cross-reactive with heterologous genogroups of sapovirus (42)(43)(44). Large-scale studies are needed to investigate whether protective immunity for sapovirus is genotype specific or not, since the number of children with reinfections in this study was small due to a limited sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Sapovirus (SaV) belongs to the family Caliciviridae and is a causative agent of gastroenteritis in children and adults (6,2). On the basis of complete capsid gene sequences, SaV can be divided into five genogroups, among which GI, GII, GIV, and GV infect humans, whereas SaV GIII infects porcine species (1).…”
mentioning
confidence: 99%